Pelatihan QRIS Sebagai Media Pembayaran Cashless Pada Masyarakat Desa Gunung Sari Kabupaten Bogor - Whendasmoro, Raditya Galih; Zulkarnain, Iskandar; Fauziyah, Fauziyah; Lestari, Dwi (LPPM Universitas Bung Karno, 2023)
QRIS (Quick Response Code Indonesian Standard) is a transaction technology that is currently in demand by the public. QRIS started to become a payment method of choice after COVID-19, which required the government to issue regulations to prevent the spread of COVID-19. In the current digital era, QRIS is increasingly developing as a digital financial transaction tool. As a tourist area, the development of MSMEs (Micro, Small and Medium Enterprises) requires the people of Gunung Sari Village, Pamijahan Subdistrict, Bogor Regency follows developments in financial technology to attract tourists to visit. Lack of knowledge about QRIS technology and QRIS security is the reason why the Lecturer and Student Team carry out training for the community. The implementation of QRIS training is expected to increase community knowledge so that QRIS technology can be utilized by the community of Gunung Sari Village, Pamijahan Subdistrict, Bogor Regency is an easy and safe means of payment, so it can attract and make it easier for tourists to make transactions and can improve the community's economy.